Microbiological quality of experimental animal - Romero Molina, María Asunción (Mexican Journal of Medical Research ICSA, 2014)
Nowadays, it is unquestionable the importance of the laboratory animal health in research. Improving the microbial quality animal allows to reduce (or eliminate) the negative effects of pathogen agents (not associated with the objective of the study) in the expected experimental results. Health monitoring programs are used as preventive tools in animal facilities, although, in some circumstances many facilities cannot or have problems for establishing appropriate strategies. The present text attempts to bring the reader’s interest to the laboratory animal health. A better awareness about this topic will allow a better use of animals in research.